ON $q$-BILATTICES - Davidova, D.S. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2011)
In this paper the concept of $q$-bilattice is studied. Interlaced $q$-bilattices are characterized by the pair of congruencies.
Keywords: $q$-semilattice; $q$-lattice; $q$-bilattice; an interlaced $q$-bilattice; hyperidentity